MUITI-OBJECTIVE OPTIMAZATION IN THE ELECTRICAL DISCHARGE MACHINING OF THE TA7 BASED ON BSO ALGORITHM - ZHANG LiXin; YANG Kang; LI YuXi (Jixie qiangdu)
For the existing EDM machine,there is no specification of titanium alloy processing standard,the design center combination experiment,comprehensive consideration of no-load voltage,peak current,pulse width and pulse interval on TA7 EDM material removal rate,surface roughness and electrode Loss rate. The prediction model of material removal rate,surface roughness and electrode loss rate was established. In order to take into account the three conflicting process objectives of material removal rate,surface roughness and electrode loss rate,a process objective optimization model was established,and the brainstorm algorithm was designed to solve the optimization model. The results show that the average relative error between the measured value of material removal rate,surface roughness and electrode loss is 5%,4. 7% and 5. 5%,respectively. The results show that the brainstorm algorithm can effectively obtain the best process parameters of TA7 titanium alloy EDM.